Respuesta :
Answer:
x=-1
Step-by-step explanation:
first you multiply 3 by whats in the parenthesis (you would get 6x-3)
then on the other side you combine like terms (add 7x plus 5x=12x)
Then you would isolate X to one side by subtracting 6x from 12x
Then you would subtract 3 from the side with 12x
By now your equation would be -6=6x
so you would divide both side by negative six to get x=-1
Answer:
x=-1
Step-by-step explanation:
3(2X-1)=5x+3+7x Distribute the 3 into the parenthesis
6x-3=5x+3+7x Isolate the x on one side
-6x -6x
-3=5x+3+7x-6x
-3 -3
-6=5x+7x-6x Add all the x's
-6=6x Divide 6 to isolate x
(-6)/6=(6x)/6
-1=x
Now you can check if it's right by inputting -1 for x and seeing if the equations equal each other
3(2(-1)-1)=5(-1)+3+7(-1)
3(-3)=-5+3-7
-9=-9 They equal each other so x=-1 is correct